Red blood cell distribution width and carotid intima-media thickness in patients with metabolic syndrome. Issue 1 (December 2017) - Ren, Dongdong; Wang, Juan; Li, Hua; Li, Yanyan; Li, Zhanzhan
Abstract Background To evaluate the relationship between red blood cell distribution width (RDW) and carotid intima-media thickness (CIMT) in metabolic syndrome (MetS) patients. Methods In this study, we analyzed 803 patients with MetS who underwent carotid ultrasonography examination at Henan Province Hospital of Traditional Chinese Medicine from October 2014 to September 2015. Demographic data were collected using a questionnaire. An automatic biochemistry analyzer measured RDW. Pearson correlation coefficient, multivariate linear and logistic regression was used to evaluate the correlation between RDW and CIMT. Results Compared with control group, case group had higher RDW level (P  < 0.001) and CIMT (P  < 0.001). CIMT was positively related to RDW (r  = 0.436, P  < 0.001). Logistic regression indicated that RDW was a predictor of CIMT ≥ 1 mm. Compared with the first quartile, people with third and fourth quartile level gave obvious higher risk of carotid artery atherosclerotic trend (OR = 1.41, 95% CI:1.01–197; OR = 2.10, 95% CI: 1.30–3.40). Using a cutoff point of 13.9%, RDW predicts elevated CIMT with a sensitivity of 62.1% and a specificity of 70.3%. Conclusion High RDW is related to the increased CIMT in MetS patients, which highlights the role of RDW in the progression of elevated CIMT in MetS patients.